The Supraclavicular Artery Flap for Lateral Skull and Scalp Defects: Effective and Efficient Alternative to Free Tissue Transfer - Hunt, Jason P.; Buchmann, Luke O. (Journal of Neurological Surgery Reports, 2014)
Objectives Describe the use of the supraclavicular artery flap for reconstruction of lateral skull and scalp defects. Discuss advantages and potential limitations of the supraclavicular artery flap.Design Case series.Setting Tertiary care academic medical center.Participants Patients undergoing lateral scalp and skull base resections.Main Outcome Measures Effectiveness in reconstructing lateral skull base defects and complications.Results All three patients reconstructed with the supraclavicular artery flap had excellent reconstructive outcomes. There were no flap losses, either complete or partial. There were no major complications, but one patient had a significant donor site dehiscence requiring local wound care. Referred sensation to the shoulder was alleviated by division of the sensory innervations into the flap.Conclusions The supraclavicular artery flap is an excellent option for lateral skull and scalp defects, and donor site morbidity is limited. It should be considered as an alternative to free tissue transfer.
Keywords: supraclavicular flap; lateral skull base; reconstruction; regional flap